Sertifikasi Halal dan Kerjasama Internasional di Era Digital Melalui Kebijakan One Roof System BPJPH - Ma’ruf, Siti Nur Azizah (LITERATUS, 2024)
Halal certification in Indonesia has a very important role, not only from a religious perspective, but also from an economic, social, and legal perspective. Before the One Roof System, halal certification tended to be inefficient, expensive, and less transparent. This hampers the development of the halal industry in Indonesia, both nationally and internationally. With the one-roof policy, it is hoped that the challenges in halal certification can be overcome through a more centralized, standardized, and transparent process. The problem is, how is the one-roof system policy implemented by BPJPH in the context of the halal certification process and international cooperation in the digital era? Because through the digitalization carried out by BPJPH with a one-roof system, there are obstacles in its regulations. Law Number 33 of 2014 concerning Halal Product Assurance and Government Regulation of the Republic of Indonesia Number 42 of 2024 concerning the Implementation of the Halal Product Assurance Sector have not regulated the one-roof system mechanism. Government Regulation Number 42 of 2024 concerning the Implementation of the Halal Product Assurance Sector does not explicitly mention the one-roof system. However, this Government Regulation implicitly supports the concept to improve the efficiency and effectiveness of the implementation of halal certification. The research method is normative legal. In conclusion, halal technology refers to the use of technology in supporting the certification process, production, distribution, and supervision of halal products. In the digital era like today, technology plays a crucial role in accelerating, simplifying, and increasing the accuracy of processes related to the halalness of products. Through the use of this digital technology, the halal certification system becomes more modern, integrated, and easily accessible to all parties. This supports the growth of a more efficient and reliable halal industry in the future.